EARLY MEDIEVAL SETTLEMENT IN THE MIZDAKHKAN SITE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
In this article, cultural layers identified as a result of archaeological excavations in the area of Gyaur Castle will help us to better study our history. A unique culture was formed here, as a result of archaeological excavations and the study of written sources, a lot of information was revealed, including handicraft production, pottery, weaving, and money circulation were again established, indicating economic well-being and the strengthening of new feudal relations. This, in turn, affected the further development of culture, writing, and applied arts.